Pemanfaatan Ekstrak Serai Dalam Pembuatan Spray Anti Nyamuk Sebagai Upaya Pencegahan Kasus DBD Di Desa Kepala Sungai - Khairani, Beby; Sanjaya, Bima; Sambas, Ela Carmelia Mukti; Indriati, Silvi; Zainarti, Zainarti (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia has experienced an increase in the number of dengue fever cases every year, including Kepala Sungai village, which is one of the areas affected by dengue fever. Dengue fever caused by the aedes aegypti mosquito presents a challenge to the community to protect themselves and their families from mosquito bites that cause dengue fever. The community service activities of the 128th Real Work Lecture (KKN) UIN North Sumatra played a role in preventing the spread of dengue fever cases in Kepala Sungai village. The research method used in this study was qualitative and creative learning which was conducted in Kepala Sungai village with research subjects. The purpose of this study was to provide practical and effective solutions in preventing dengue fever cases in Kepala Sungai village. The results of the study stated that lemongrass plant extract has very large benefits and roles in reducing dengue fever cases in Kepala Sungai village. Through a mixture of ethanol with a content of 70% and various stages carried out, a simple innovation was produced, namely anti-mosquito spray from lemongrass. Keywords: Lemongrass, DBD, Anti-mosquito spray